Prevalencia de anemia infantil y factores socioculturales de las usuarias del Programa Juntos, distrito de Pampas - Alarcón Soto, Olivia (2019)
This research aimed to measure the level of influence of sociocultural factors of the users of the Juntos Program on the prevalence of childhood anemia at the Pampas Hospital (Tayacaja, Huancavelica). An investigation of basic type, descriptive level, transversal non-experimental design and with a quantitative methodological approach was carried out. A questionnaire was applied to 36 mothers using the Together Program; the children of 16 of these have a prevalence of anemia, and those of the remaining 16, no. At 95% statistical confidence, the results obtained were: 82% of mothers whose children have anemia are under 30 years of age; the children of 71% of mothers, who mostly come from the rural area, have a prevalence of childhood anemia; 68% of mothers have conflicts with their children's parents; Only 23% of mothers who have access to public services with drinking water are less recurrent to the prevalence of anemia; 76% of them participate in other social programs, and 77% of the same trust in the health system. It is concluded that the social factors in the users of the program together of the Pampas hospital, Tayacaja directly and significantly influence the prevalence of childhood anemia, the mother's behavior, her living conditions, the iteration with her youngest child. and with the group of personnel that socialize every day, it generates a lifestyle that does not contribute to overcoming the diagnosis of anemia and they become prevalent, directly affecting the physical and emotional development of the infant, this situation compromises its future, promoting scenario that becomes negative for human development, the generation of social capital, and consequently for social development. Cultural factors in the users of the program together at the Pampas, Tayacaja hospital directly and significantly influence the prevalence of childhood anemia, the habits and daily habits of the mother's behavior in her surroundings, the elements that guide the coexistence with her Younger child, a generates a culture of coexistence that does not contribute to the overcoming of the diagnosis of anemia but on the contrary they are presented as prevalent, this way of seeing life, the assessment of the health situation are influenced by the way If you conceive the world, your idiosyncrasy does not allow you to easily assume the situation of importance and priority of child care with eating habits and hygiene more appropriate to the treatment of childhood anemia.   DOI: https://doi.org/10.31876/sl.v1i1.63